MAKNA KAFIR DALAM TAFSIR MUHAMMADIYAH: STUDI ANALISIS KOMPARATIF - Nurrohim Ahmad; An-Najmi Fikri R (Universitas Muhammadiyah Surakarta, 2021)
The controversy of kafir term for non-Muslims was debated in 2019. The debate originated from Nahdlatul Ulama National Conference that discussed kafir term is considered to contain theological violence (insult). The kafir interpretation raises various perspectives and views from Islamic institutions as Muhammadiyah. As a moderate Islamic organization in Indonesia, Muhammadiyah has its own interpretation to explain kafir in the Al-Qur'an. The institutional interpretation books written by Muhammadiyah collectively include Tafsir Al-Qoer'an Djoez ke Satoe and Tafsir At-Tanwir. This study aims to compare the meaning of kafir in the two Muhammadiyah interpretations. The data were collected using the documentary method and analyzed using the comparative analysis method. The results showed that the interpretation of the word kafir in the Muhammadiyah institutional interpretation books experienced a positive expansion from the theological meaning to the linguistic meaning.